ZnFe2O4 nanoparticles prepared using the hydrothermal and the sol-gel methods - Lestari, Kiki Rezki; Yoo, Pilsun; Kim, Deok Hyon; Liu, Chunli; Lee, Bo Wha (Journal of the Korean Physical Society, 2015)
Zinc-ferrite nanoparticles were prepared using the hydrothermal and the sol-gel methods. ZnFe 2 O 4 nanoparticles with a spinel structure were formed by using both approaches, which was confirmed through X-ray diffraction. Although both types of ZnFe 2 O 4 nanoparticles showed similar morphologies and particle sizes, the saturation magnetization of the ZnFe 2 O 4 prepared using the hydrothermal method was about 10 times higher than that of the ZnFe 2 O 4 prepared using the sol-gel method. Through the Rietveld refinement analysis, we were able to conclude that the enhanced magnetic property of ZnFe 2 O 4 could be attributed to the cation inversion induced during the hydrothermal synthesis process.